DC's legends of tomorrow. The seventh and final season [videorecording (DVD)] - Berlanti, Greg; Guggenheim, Marc; Kreisberg, Andrew, 1971-; Klemmer, Phil (Warner Bros. Entertainment Inc., 2022)
After saving the planet from the alien horde last season, the Legends find themselves stranded in 1925 Texas with no way home. Determined to return to their own time, the Legends set out on a road-trip across the country to find an early pioneer of time travel, and their only hope of returning to their home time once more!